A Comprehensive & Investigative Review of Literature on Digital Image Processing Technique for Multidisciplinary Industrial Application - Naqvi, Syed Faraz Ahmed; Niwaria, Kamal; Chourasia, Bharti (International Journal of Computer Sciences and Engineering, 2019)
In the era of digital communication, digital image play a important role in most of industrial and corporate forensic applications. Digital imaging has experienced unremarkable revolution in recent decades, and digital images have been used in a increasing number of applications. Digital Images are used as authenticated proof for any crime and if these images do not remain veritable then it will create question on the validation process. Detecting these types of faking has become serious issue. To determine whether a digital image is original or fake is a big challenge. The detection of image meddling in a digital image is a challenging task. This paper presents a literature survey on some of the image influence detection techniques such as image pre-processing, image compression, edge detection, segmentation, contrast enhancement detection, splicing and composition detection, image tampering and more. Comparison of all the techniques finds the better approach for its future research.